Efektivitas Penggunaan Media Digital Google Form dalam Evaluasi Belajar Siswa - Fitriani, Fitriani; Jamin, Hanifuddin; Abidah, Abidah (Mitra PGMI: Jurnal Kependidikan MI, 2024)
In this digital era, the student evaluation process can be carried out anywhere and at any time, this makes teachers think creatively about using information and communication technology in student evaluation activities. One method used by teachers in the student evaluation process is by using the Google Form application. This research is about "Effectiveness of Using Digital Media in Evaluation of Student Learning at MIS Nurul Falah, West Aceh Regency". The aim of this research is to determine the effectiveness of using Google Form digital media in evaluating student learning at MIS Nurul Falah, West Aceh Regency. This research uses a quantitative approach and the type of research used is descriptive research. Data collection techniques in this research are observation, questionnaires, interviews and documentation. The results of this research can be concluded that the use of Google Form digital media in evaluating student learning at MIS Nurul Falah, West Aceh Regency is considered very effective with a percentage of 84.8%. Therefore, Google Form evaluation media can be an evaluation media option that is considered effective, practical and efficient when it is used in learning.